What does it mean to follow? Movements in harmolodic space - James, Alex (2022)
“You follow me”, says Ornette to Charlie Haden at one of their first meetings, sometime in the later 1950s, “and you go where I go”. But what does it mean to follow Ornette, what does it mean to go where Ornette goes? Oriented by tools developed from psychoanalysis – in particular the notion of transference, with its roots in the philosophy of the Scottish Enlightenment – as well as tools from a Lacanian Discourse Analysis and the neighbourhood topology of Felix Hausdorff, we attempt to lend a psychoanalytic ear to Ornette's discourse, finding in its many allusions to relations and their impasses – musical and otherwise – new ways to listen to Ornette's music as structure and space, as well as movements through that space. If we follow Ornette, attempting to go where Ornette goes, we also find in his thought consequences that offer the means to go further, to think with Ornette, beyond where his thought has already gone. In this way, we “take part”, as Freud says of the aims of the psychoanalytic experience, “in building up a new theory of the subject”.